STRUKTUR POPULASI LABI-LABI (Amyda cartilaginea) DI DANAU ULAK KERAMAT KABUPATEN KAPUAS HULU - Sidit, Oktavianus; Soetignya, Widadi Padmarsari; Anzani, Yunita Magrima (Jurnal Sains Pertanian Equator, 2025)
The Asiatic softshell turtle (Amyda cartilaginea) is a species of freshwater turtle that has been classified as vulnerable by the IUCN and inhabits rivers and lakes. Its utilization has been practiced for a long time, whether for food, traditional medicine, or as pets, which can disrupt the turtle's population. This study aims to examine the population structure, consisting of abundance and size distribution, growth patterns, sex ratio, and age structure, which can later serve as scientific information for conservation efforts. The research was conducted from July to August 2024 in Ulak Keramat Lake, Bika Subdistrict, Kapuas Hulu Regency. The data collected included curved carapace length (CCL), curved carapace width (CCW), weight, sex, and environmental conditions. Subsequently, the data were analyzed to determine abundance and size distribution, growth patterns, sex ratio, age structure, and diet. The study obtained 30 turtles with a CCL of 15"“70 cm, CCW of 14"“53 cm, and a weight of 0.3"“32 kg, exhibiting a positively allometric growth pattern (b=3.0922). The male-to-female ratio was 1.27:1, with the age structure dominated by adult turtles (67%). The lake environment was in good condition and supported the turtle's habitat.